STIGMA MAHASISWA KEBIDANAN DAN KEPERAWATAN TERHADAP ORANG DENGAN HIV/AIDS (ODHA) DI KABUPATEN KEBUMEN - Galuh Ismah Nur Awalis; Besar Tirto Husodo; Syamsulhuda B Musthofa (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
One of the things that challenges HIV/AIDS reduction is stigma and vice versa for people with HIV/AIDS (PLWHA). The most stigma and contribution to health services. Health students who are expelled will fall into health services which are expected to be able to reject the stigma against PLWHA. The impact of the existence of stigma on people with HIV/AIDS (PLWHA) is that sufferers who withdraw from the community, do not want to do routine maintenance for fear of being open. The purpose of this study was to study the stigma of midwifery and nursing students towards people with HIV/AIDS (PLWHA). This research method is quantitative research with cross sectional research design. The sample in this study was active midwifery and nursing students level 1 to 3 in Kebumen Regency, taken using the simple random sampling method with a total number of respondents as many as 89 people. Data collection was carried out through the interview method using a questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed that there was a relationship between force variables, age variables, participation variables with PLWHA, courses, access to information, knowledge and attitudes towards PLWHA with the stigma of midwifery and nursing students towards people with HIV/AIDS (PLWHA) in Kebumen Regency. the results of this study there is still a stigma against PLWHA in midwifery and nursing students namely with the category of stigma against PLWHA low category (73%) and stigma against PLWHA high category (27%).